Creating Effective Quizzes by Balancing the Distribution of Question Types - Ilijoski, Bojan; Popeska, Zaneta; Stankov, Emil (IATED, 2018)
The creation of quizzes as a method of student evaluation is a complex process. Quizzes are very convenient method of evaluation when the number of students is large and the deadline is close, especially if the reviewing is organized as e-testing. In that case a teacher must choose appropriate questions in order to get the right picture of student’s acquired knowledge. Usually those tests are based on questions which are single or multiple choice, dropdowns etc. in one hand and short/essay answers in another. In the first group there is possibility for random guessing and the offered answers to these questions can be very similar and sometimes confusing which can lead students that know the material to select the wrong answer. Also the answers can be drastically different and completely disjunctive so the correct answer is very predictable.Short answer/essay questions cancel these shortcoming. But, when we have short/essay answers one of the main drawbacks is that they must be manually graded, which can be very time consuming and subjective. This article will present the comparison of efficiency between the answers on single choice, multiple choice and short answer/essay questions in several courses in the IT field. The idea is to find the correlation between those two groups of answers, compare the average scores between them and estimate the minimal percent of short answer/essay questions that is necessary to grade a student. The solution will help with creating efficient quizzes so teachers can get plausible tool for estimation of student knowledge.